2012
DOI: 10.1016/j.ijgo.2011.12.020
|View full text |Cite
|
Sign up to set email alerts
|

The effect of traditional birth attendant training on maternal and neonatal care

Abstract: SMART Dai training seemed to be an important factor in the significant reduction in perinatal mortality in the CBI areas. Properly trained TBAs can substantially contribute to improved delivery outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Future research should investigate combined social and medical models. Despite the concerns regarding such integration, appropriately trained traditional healers are helpful to promote health among the rural communities in LMIC (Freeman and Motsei, 1992;Miller et al, 2012). Infectious diseases still add to the out-of-pocket health expenditure for older people in LMIC.…”
Section: Need For Equitable Health Servicesmentioning
confidence: 99%
“…Future research should investigate combined social and medical models. Despite the concerns regarding such integration, appropriately trained traditional healers are helpful to promote health among the rural communities in LMIC (Freeman and Motsei, 1992;Miller et al, 2012). Infectious diseases still add to the out-of-pocket health expenditure for older people in LMIC.…”
Section: Need For Equitable Health Servicesmentioning
confidence: 99%
“…Frontline health workers include volunteer community health workers, traditional birth attendants (TBAs), as well as a variety of other paid paraprofessionals (eg, health extension workers and lady health workers) who attend women during pregnancy or during the birth and/or provide health education. It has been shown that the extension of maternal and newborn health care by trained health workers yields improved care provision and self‐care behaviors and often contributes to better birth outcomes and reduced neonatal mortality . While most studies have shown positive outcomes, some have not.…”
Section: Introductionmentioning
confidence: 99%
“…Health worker training programs have used a number of strategies to evaluate and demonstrate change in health workers’ skills and knowledge. Evaluation efforts have entailed (solely or in combination) pre‐ and posttraining knowledge tests, observation of skills by trainers, objective simulated clinical examinations, health worker self‐reports, and interviews with end users (community members who are the intended recipients of the care/education) . Some have also conducted evaluations a while after the posttraining to assess retention of knowledge and skills over time .…”
Section: Introductionmentioning
confidence: 99%
“…Our findings can be compared with others from the literature in Guatemala and elsewhere. For example, several studies have demonstrated that lay midwives can be trained to provide some elements of neonatal care with improvements in selected outcomes, including early neonatal referrals 13–17. A large multisite trial that included Guatemala trained lay midwives and other community-based providers on essential newborn care and neonatal resuscitation, it reduced stillbirth but not neonatal death rate and did not assess for changes in neonatal referral patterns 28.…”
Section: Lessons and Limitationsmentioning
confidence: 99%
“…In this project, our goal was to use this existing practice network of lay midwives and mHealth platform to improve the quality of care for neonates. Several studies have demonstrated that lay midwives in various contexts can be trained to provide elements of neonatal care with improvements in outcomes, including early neonatal referrals 13–17. In addition, others have studied using mHealth to improve care for neonates in low resource settings.…”
Section: Introductionmentioning
confidence: 99%